Pengaruh Model Pembelajaran Children’s Learning in Science berbantuan Media Audio Visual terhadap Kompetensi Pengetahuan IPA - Rositayani, N P E; Putra, D B K N S; Abadi, I B G S (Universitas Pendidikan Ganesha, 2018)
The purpose of this research was to know the significant difference of science knowledge competence between students who taught using learning model of children's learning in science assisted by audio visual media and students who taught using conventional learning in fourth grade students of SD Gugus Untung Surapati Denpasar Timur. The type of this research was quantitative research with quasi-experimental design with nonequivalent control group design. Population of this research were all student of fourth grade of elementary school of Gugus Untung Surapati Denpasar Timur as 205 students. Sampling using random sampling technique. The sample of this research was the fourth grader of SD Negeri 9 Sumerta which used as experimental group and fourth grade students of SD Negeri 6 Sumerta which become the control group. Data on the competence of science students knowledge of grade IV is collected by using the instrument of ordinary double choice objective test. Based on the result of data analysis, the average gain of experiment group score (X ̅_1) and control group (X ̅_2), that is 0,57 > 0,45 Through hypothesis test obtained thitung> ttable, that is 2,4 > 1,994 with dk = 70 and significance level 5% then Ho reject and Ha accept. Thus it can be concluded that the learning model of children's learning in science assist audio visual media influence on science knowledge competence of fourth grade students of SD.